Gender and Governance in Agricultural Extension Services : Insights from India, Ghana, and Ethiopia - Madhvani, Sonia (Washington, DC: World Bank, 2012)
The gender and governance in rural services insights from India, Ghana, and Ethiopia report aims to generate policy-relevant knowledge on strategies for improving agricultural service delivery, with a focus on providing more equitable access to these services, especially for women. The project has been implemented in India, Ghana, and Ethiopia. These countries were chosen to capture variation in important macro-factors, especially the level of economic development; various aspects of governance, such as political system and party system; the role of women in society; and strategies adopted to promote gender equity. The project focused on agricultural extension as an example of a critical agricultural service. In India, the main problem is the lack of overall capacity resulting from a past policy of not hiring agricultural extension providers. The study indicates that access to agricultural extension is low in Ghana, despite the fact that an extension agent-to-farmer ratio is comparatively high. Agricultural extension is a high for the Ethiopia government priority, but coverage of extension services across regions varies widely, and extension agents have limited discretion to adapt technology packages to the context of individual communities. The gender gap in access to extension can also be improved.